Exercise and the Brain: Lessons From Invertebrate Studies - Dyakonova, Varvara; Mezheritskiy, Maxim; Boguslavsky, Dmitri; Dyakonova, Taisia; Chistopolsky, Ilya; Ito, Etsuro; Zakharov, Igor (Frontiers in Behavioral Neuroscience, 2022)
Benefits of physical exercise for brain functions are well documented in mammals, including humans. In this review, we will summarize recent research on the effects of species-specific intense locomotion on behavior and brain functions of different invertebrates. Special emphasis is made on understanding the biological significance of these effects as well as underlying cellular and molecular mechanisms. The results obtained in three distantly related clades of protostomes, Nematodes, Molluscs and Artropods, suggest that influence of intense locomotion on the brain could have deep roots in evolution and wide adaptive significance. In C. elegance, improved learning, nerve regeneration, resistance to neurodegenerative processes were detected after physical activity; in L. stagnalis – facilitation of decision making in the novel environment, in Drosophila – increased endurance, improved sleep and feeding behavior, in G. bimaculatus – improved orientation in conspecific phonotaxis, enhanced aggressiveness, higher mating success, resistance to some disturbing stimuli. Many of these effects have previously been described in mammals as beneficial results of running, suggesting certain similarity between distantly-related species. Our hypothesis posits that the above modulation of cognitive functions results from changes in the organism's predictive model. Intense movement is interpreted by the organism as predictive of change, in anticipation of which adjustments need to be made. Identifying the physiological and molecular mechanisms behind these adjustments is easier in experiments in invertebrates and may lead to the discovery of novel neurobiological mechanisms for regulation and correction of cognitive and emotional status.